Execution of Criminal Acts of Fines Can Not Be Fulfilled by Convicts in Mining Crimes - Hermann; Oheo Kaimuddin Haris; Ali Rizky; Elinda Nur Hidayah (Simbur Cahaya, 2025)
This study aims to analyze criminal legal instruments for fines that have passed the grace period in the mining sector and the implementation of criminal fines for convicts who have passed the grace period by the principle of legal certainty. This research and writing method applies empirical Law with a conceptual approach, principles, criminal law theory, law approach, and case approach. This study produces and answers the legal issue that the emergence can also see the application of fine penalties and the tendency to apply prison sentences cumulatively with prison sentences. The type of criminal sanction in the mineral and coal law is the main crime in Imprisonment, a fine, and Imprisonment. If the perpetrator is a legal entity, the type of fine sanction for the legal entity is plus 1/3 of the maximum criminal provisions of the fine imposed. Additional crimes include revoking business licenses and/or revoking legal entity status. Criminal liability in the mining sector can be imposed on individuals or legal entities as can be reviewed from the subject of criminal acts contained in the criminal provisions. The following finding is that the application of criminal sanctions and fines in criminal acts in the mining sector still raises problems; namely, there is a gap between criminal sanctions and fines in the formulation of the mining law due to the absence of explicit rules on the mechanism of coercive efforts so that the convict can carry out the fine imposed sentence. The existence of a criminal law option of fines can be replaced by prison sentences, causing many convicts to choose to serve prison sentences instead of fines. By serving a prison sentence, it is as if the convict has paid the fine in full.